The Impact of Financial Structure on Firm Performance: A Study of Nigeria Agricultural and Healthcare Sector - , Echekoba Felix Nwaolisa; , Ananwude Amalachukwu Chijindu (Archives of Current Research International, 2016)
This study examines the impact of financial structure on performance of agricultural and healthcare firms listed in Nigerian Stock Exchange for a period of twenty one (21) years 1993 to 2013. This study selected fifteen (15) out of the sixteen (16) firms listed on agricultural and healthcare sectors. Data were collected from the Nigerian Stock Exchange factbook of various issues as relevant and were analysed using the pooled OLS, fixed, random effect models and the granger causality test. Financial structure was surrogated by total debt to total equity ratio, short term debt to total equity and total debt to total assets ratio while firm performance was measured by return on assets, return on equity, earnings per share and profit before tax. The analysis for the agricultural firms revealed that financial structure significantly impacts on earnings per share but does not impact on return on equity, return on asset and profit before tax. For healthcare firms, financial structure significantly impacts on earnings per share and profit before tax but does not impact on return on equity and return on assets. On the impact of the control variables on performance, it was observed that it is only risk that is significant in determining performance of agricultural firms while tangibility, size, growth and tax are significant factors that impact on performance of healthcare firms. To this effect, we suggests that it is very crucial for firm’s management to carefully look at the debt-equity mix, which according to the result of the study, significantly impacts on performance of firms in agricultural and healthcare sectors.